Neopagan groups in Portugal: The ethnographic case of the 1st Goddess Conference in Portugal - Martins, Joana. (Summer School 'Religion in Public Spaces', 2019)
Presentation of preliminary findings regarding the fieldwork done during the 1st Goddess Conference in Portugal 2019 for my PhD research on Neopagan groups in Portugal and United Kingdom